Sobre semigrupos numéricos - Silva, Marcela Diniz (2022)
A numerical semigroup is a submonoid of non-negative integers whose complement on this set is finite. We shall study basic concepts about numerical semigroups in N and some characterizations, in particular the irreducibility and almost symmetry, that are generalized fornumerical semigroups in Nd, with d a positive integer greater than 1.